ANALISIS PENGARUH CITRA MEREK DAN KUALITAS LAYANAN SERVICE CENTER TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (Studi Kasus: Nokia Care Center Wilayah Jakarta) - Gerry Sasongko (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: This thesis aims to find out about the influence of brand image, service quality and customer satisfaction to customer loyalty from Nokia phone users across Jakarta area. The method used in this study is a descriptive analysis of the census data collection system through the use of questionnaires to the respondents. Respondents in this study amounted to 200 people. Data processing technique and analysis of themodel using SPSS version 20 and the Structural Equation Model (SEM) with Lisrel 8.7 program. From the results of this study, brand image affects customer satisfaction. Service quality has a positive effect on customer satisfaction. Brand image affects customer loyalty. Service quality has a positive effect on customer loyalty. And customer satisfaction have an effect on customer loyalty.Keywords: brand image, service quality, customer satisfaction, customer loyalty